The Impact of Religiousity To Preferences of Muslim‘s Investor In Capital Market - Rinda Asytuti (Jurnal Hukum Islam, 2016)
The current study aims at knowing know how far a religiosity affects a person’s behavior in the capital market. This qualitative research uses the religiosity theory constructed by Glork and Start. These results from the interview to 3 investors as the subjects of the research shows that the religiosity of Muslim investors in Pekalongan is not automatically guarantee their invesment behaviors. This research support the previous research conclusion that religiousity not automaticaly conducted muslim investment behavior in banking and finance. On the other hand there are some research have different conclusion.